Preparation method and application of sea urchin-shaped ZnSe / ZnS quantum dots
The synthesis of sea urchin-shaped ZnSe/ZnS quantum dots addresses the challenge of achieving a blue light emission peak by increasing crystal size, resulting in efficient and stable quantum dots for display applications.
Patent Information
- Application Number
- CN202411284030.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
Existing methods struggle to synthesize pure blue-light emitting ZnSe quantum dots due to challenges in growing crystal size, necessitating new approaches to achieve the desired emission peak in the blue light range.
A method involving the preparation of sea urchin-shaped ZnSe/ZnS quantum dots through specific precursor injections and controlled temperature conditions, including the use of Se-DPP, Zn, and TOP-S precursors, results in a larger crystal core coated with a ZnS shell, achieving a luminescence peak of 460nm.
The method enables the production of quantum dots with enhanced heat dissipation and electroluminescent performance, suitable for high brightness displays, with improved stability and efficiency.
Smart Images

Figure CN119144332A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to a preparation method and application of sea urchin-shaped ZnSe / ZnS quantum dots. Background Art
[0002] Colloidal quantum dots (QDs) are a new type of nano-sized material. Due to its advantages such as adjustable band gap, wide color gamut, narrow half-width (FWHM), low synthesis cost and compatibility with traditional device structures, it has good performance in the display field. In the past decade, the synthesis of red, green and blue quantum dots and the preparation of LED devices based on quantum dots as the light-emitting layer have developed rapidly, and the highest external quantum efficiencies (EQEs) of the three have exceeded 20%. According to the RoHS agreement, quantum dots based on toxic heavy metal Cd are restricted from widespread use, and cadmium-free InP and ZnSe quantum dots came into being. Among them, ZnSe is regarded as an ideal blue light quantum dot material because its intrinsic band gap is about 2.7ev, resulting in its intrinsic emission peak position of pure blue light at 460nm (455-470nm).
[0003] The widely reported blue-light emitting ZnSe quantum dots often have an emission wavelength of around 440nm, which is blue-violet and harmful to human eyes. Pure blue-light ZnSe quantum dots are needed to replace it. However, synthesizing pure blue-light ZnSe quantum dots is still a challenge because if the quantum dot emission peak is to be blue-shifted, it needs to be achieved by growing the crystal size, and it is difficult to further grow the crystal using common synthesis methods, which means that new methods are needed to obtain pure blue-light quantum dots. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a preparation method and application of sea urchin-shaped ZnSe / ZnS quantum dots.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing sea urchin-shaped ZnSe / ZnS quantum dots comprises the following steps:
[0007] Step 1: Prepare ZnSe seeds using Se-DPP precursor;
[0008] Step 2: injecting Zn and Se precursors dissolved in ODE into the ZnSe seed solution prepared in step 1 to obtain ZnSe cores;
[0009] Step 3: Inject TOP-S precursor and OT precursor into the ZnSe core solution prepared in step 2 respectively to obtain sea urchin-shaped ZnSe / ZnS quantum dots.
[0010] Preferably, in step 1, the specific method of preparing ZnSe seed crystals is: injecting Se-DPP precursor into a mixed solution of zinc acetate, oleic acid, oleylamine and liquid paraffin.
[0011] Preferably, when the Se-DPP precursor is injected, the temperature is stabilized at 280-320°C.
[0012] Preferably, in step 2, during the preparation of the ZnSe core, the temperature is maintained at 280-320° C., and the volume ratio of the injected Zn precursor mixture dissolved in ODE to the injected Se precursor mixture dissolved in ODE is (4-6):(2-3).
[0013] Preferably, in step 3, the temperature when injecting the TOP-S precursor is maintained at 280-320°C; the temperature when injecting the OT precursor is maintained at 260-300°C.
[0014] Preferably, in step 3, the volume ratio of the injected amounts of TOP-S precursor and OT precursor is (2-3):(4-6).
[0015] An application of sea urchin-shaped ZnSe / ZnS quantum dots, wherein the sea urchin-shaped ZnSe / ZnS quantum dots are prepared by the method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to any one of claims 1 to 6, and the application of the sea urchin-shaped ZnSe / ZnS quantum dots in a light-emitting device.
[0016] Preferably, the structure of the light-emitting device is ITO (indium tin oxide) / PEDOT:PSS [poly (3,4-ethylenedioxythiophene) / poly (styrene sulfonate)] / TFB {poly [(9,9-di-n-octylfluorenyl-2,7-diyl) -alt- (4,4'- (N- (4-n-butyl) phenyl) -diphenylamine)]} / quantum dots / PO-T2T {2,4,6-tris [3- (diphenylphosphino) phenyl] -1,3,5-triazine} / LiF / Al.
[0017] Preferably, the method for preparing the light-emitting device comprises the following steps: firstly, in a nitrogen atmosphere, preparing the hole transport layer PEDOT:PSS and TFB layer of the device by spin coating on the etched ITO conductive glass; then preparing the quantum dot layer by spin coating; then, -7 Under the high vacuum of the tortoise, the device's electron transport layer PO-T2T and electrode LiF / Al layer are sequentially evaporated into films by a thermal evaporation system.
[0018] Preferably, the rotation speed of spin coating PEDOT:PSS, TFB and quantum dot layers is 1000-4000 r / min, and the spin coating time is 30-60 s; the thickness of the evaporated PO-T2T layer is 20-60 nm, the thickness of the evaporated LiF layer is 1-2 nm, and the thickness of the evaporated Al layer is 80-150 nm.
[0019] The beneficial effects of the present invention are:
[0020] The present invention realizes anisotropic heterogeneous growth of nanocrystals by increasing the reaction temperature. The size of the nanocrystals finally formed reaches 13nm, the luminescence peak reaches 460nm, and this quantum dot has good performance in electroluminescent applications. At the same time, the larger specific surface area also contributes to the rapid transmission and dissipation of heat and charge. For displays working under high brightness and high power conditions, this improvement in heat dissipation performance can extend the life of quantum dots and maintain the long-term stability and performance of the display; and the preparation method of the sea urchin-shaped ZnSe / ZnS quantum dots provided by the present invention requires shorter synthesis time and higher synthesis efficiency; the quantum dots synthesized by this method have luminescence that meets the requirements of healthy display and have good electroluminescent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The quantum dot absorption and emission spectra and solution images obtained in Examples 1, 2, and 3;
[0022] Figure 2 is the transmission electron microscope image of the quantum dots obtained in Examples 1, 2, and 3;
[0023] Figure 3 This is the structure and performance diagram of the LED device using ZnSe / ZnS quantum dots as the light-emitting layer obtained in Example 4. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0025] A method for preparing sea urchin-shaped ZnSe / ZnS quantum dots comprises the following steps:
[0026] Step 1: Prepare ZnSe seeds using Se-DPP precursor;
[0027] Step 2: injecting Zn and Se precursors dissolved in ODE into the ZnSe seed solution prepared in step 1 to obtain ZnSe cores;
[0028] Step 3: Inject TOP-S precursor and OT precursor into the ZnSe core solution prepared in step 2 respectively to obtain sea urchin-shaped ZnSe / ZnS quantum dots.
[0029] The preparation principle is: first, by using diphenylphosphine (DPP) and octadecene (ODE) as ligands of Se precursors, a large-sized ZnSe crystal core is synthesized. The average size of the crystal core reaches 8nm, and its luminescence peak reaches 443nm, which has basically reached the maximum size that ZnSe / ZnS quantum dots reported in the past can achieve. Then, by using TOP-S and OT precursors to coat the crystal core with a ZnS shell, coating the ZnSe crystal core with a thick ZnS shell can passivate the surface defects of the ZnSe crystal core and increase stability; and the average size of the quantum dots after shelling reaches 13nm, and the luminescence peak reaches 460nm, which meets the requirements of healthy display for blue light.
[0030] The preparation method of the above-mentioned sea urchin-shaped ZnSe / ZnS quantum dots comprises the following specific preparation steps:
[0031] S1: Se-DPP precursor, Se-ODE precursor, TOP-S precursor, Zn precursor and O precursor were prepared respectively, and Se-ODE precursor, Zn precursor and OT precursor were stored at a constant temperature of 80°C under N2 atmosphere;
[0032] S2: Zn(OAc)2 is dissolved into liquid paraffin, and the temperature is raised to rapidly inject Se-DPP to form ZnSe seed crystals;
[0033] S3: keeping the temperature constant, adding a mixture of a Zn precursor and a Se-ODE precursor to the above ZnSe seed crystal solution to prepare ZnSe crystal nuclei;
[0034] S4: Keeping the temperature constant, add TOP-S precursor to the above ZnSe crystal core solution;
[0035] S5: Cool the above solution, add OT precursor, and cool to room temperature.
[0036] In addition, due to the continuous addition of precursors, the concentration of monomers in the solution increases, and the crystals continue to grow, from 3.5 nm in step S2 to 8 nm in step S3 and then to the final 13 nm ZnSe / ZnS quantum dots.
[0037] The highly reactive ligands give the seeds a larger critical nucleation radius, thus providing a basis for subsequent growth to 13 nm. In some instances, increasing the amount of TOP-S is beneficial to further increase the size.
[0038] Example 1: In a glove box, 0.1mmol Se powder was dissolved in 0.25mL DPP, and the mixture was stirred with a magnetic rotor until it became a colorless and transparent solution. At the same time, 0.2mmol Zn(OAc)2, 100uL OA, 500uL OLA, and 5mL liquid paraffin were added to a 100mL three-necked flask, stirred (700r / min) and heated to 120℃ under vacuum, and kept at this temperature for 40 minutes. Then nitrogen was filled, the solution was heated to 320℃, and 0.25mL Se-DPP precursor was quickly injected when the temperature reached 300℃, and the mixture was kept at 320℃ for 30min to fully react. The sample after the reaction in this example was cooled to room temperature and taken out, and n-hexane and ethanol were added in a ratio of 1:1.5 and 1:2 respectively, and centrifuged at 10000rpm / min for 8min, and the supernatant was discarded to obtain a precipitate, which was dispersed in n-hexane. This sample was tested using a fiber optic spectrometer and a transmission electron microscope, and the results showed that the average diameter of the sample was about 3.5nm and the luminescence peak was 423nm.
[0039] Example 2: First, 4mmol Zn(OAc)2, 1.5mL OA, 1.5mL OLA, and 7mL ODE were added to a 100mL three-necked flask, stirred (700r / min), slowly heated to 120°C under vacuum, and kept at this temperature for 40 minutes. Then nitrogen was charged, and the mixed solution was heated to 160°C and kept for 10min until the solution turned transparent light yellow. The cooled Zn precursor solution was kept in a nitrogen atmosphere for use. At the same time, 2mmol Se powder and 5mL ODE were added to a three-necked flask, stirred (700r / min), and after nitrogen was charged, the mixture was heated to 220°C and kept for 30min, and then heated to 260°C and kept for 10 minutes until the solution turned transparent dark brown. The cooled Se precursor solution was stored in a nitrogen atmosphere for use. The sample after the reaction in Example 1 was kept at a high temperature of 320°C, and the mixture of the Zn precursor and the Se precursor was heated to 100°C to dissolve the precipitate, and they were continuously injected (0.5mL / min) into the above-mentioned reacting solution. The sample after the reaction in this example was cooled to room temperature and then taken out, and n-hexane and ethanol were added in a ratio of 1:1 and 1:2 respectively, and centrifuged at 8000rpm / min for 8min, and the supernatant was discarded to obtain a precipitate, which was dispersed in n-hexane. This sample was tested with a fiber optic spectrometer and a transmission electron microscope, and the results showed that the average diameter of the sample was about 8nm, and the luminescence peak was 443nm.
[0040] Example 3: 2.1mmol S powder and 10.5mL TOP were mixed and stirred with a magnetic rotor until colorless and transparent to obtain a TOP-S precursor. 4mmol Zn(OAc)2, 0.7mL OT, 1.5mL OLA and 35.6mL ODE were added to a 100mL three-necked flask, stirred (700r / min) and heated to 120°C in vacuum for 40min. When the mixture became colorless and transparent, it was cooled to room temperature and sealed in a nitrogen atmosphere to obtain an OT precursor. The TOP-S precursor was continuously injected (1mL / min) into the above-mentioned reacting solution and reacted for an additional 30min. After the reaction was completed, it was cooled to 300°C for coating with a second shell. The above-mentioned OT precursor was continuously injected (0.3mL / min), and then the solution was naturally cooled to room temperature to complete the reaction. The sample after the reaction in this embodiment was centrifuged at 8000r / min to remove impurities, and then the solution was added with n-hexane and ethanol in a ratio of 1:1 and 1:2 respectively, and centrifuged at 8000rpm / min for 8min, and the supernatant was discarded to obtain a precipitate, which was dispersed in n-hexane. After this method was repeated twice, the precipitate was dispersed in octane for later use. This sample was tested with a fiber optic spectrometer and a transmission electron microscope, and the results showed that the average diameter of the sample was about 13nm, and the luminescence peak position was 460nm.
[0041] Example 4: The quantum dots obtained in Example 1 were used as the light-emitting layer to prepare an LED device. The device was manufactured based on the ITO / PEDOT:PSS / TFB / PVK / QDs / POT2T / LiF / Al structure. PEDOT:PSS (filtered through a 0.45 μm N66 filter) was spin-coated onto an ITO-coated glass substrate at 4000 r / min for 40 seconds and annealed at 150°C for 15 minutes. The PEDOT:PSS-coated substrate was transferred to a nitrogen atmosphere glove box. TFB (chlorobenzene solution, 3 mg / mL) was spin-coated onto the PEDOT:PSS film at 4000 r / min for 40 seconds and annealed at 150°C for 10 minutes. PVK (1.5 mg / mL in chlorobenzene) and quantum dots (in octane, optical density: 8) were spin-coated layer by layer at 2000 r / min for 40 seconds, wherein the PVK was annealed at 150°C for 10 minutes. Finally, a POT2T layer (40 nm), a LiF layer (1.5 nm), and an Al electrode (120 nm) were deposited using a thermal evaporation system at a high vacuum of 6.5 × 10-7 Torr. The device area is 4 mm 2 , defined by the overlapping area of the ITO and Ag electrodes. The maximum EQE of the device was tested to be 2.8%.
[0042] Description of the chemical substances involved: 1-octadecene (ODE 90%), oleic acid (OA 90%), oleylamine (OLA 90%), octanethiol (OT 98%), diphenylphosphine (DPP 98%), trioctylphosphine (TOP 90%), zinc acetate (Zn(OAc) 2 99.99%), selenium (Se 99.99% powder), sulfur (S 99.99% powder), n-hexane, ethanol, octane, liquid paraffin.
[0043] Depend on Figure 1 It can be seen that as the size of quantum dots increases, the peak position red-shifts to 460nm. The subsequent X-ray diffraction analysis (XRD) reveals the diffraction peak position of quantum dots and the movement of the peak position. According to the PDF card, the obtained nanocrystals are ZnSe, and the peak position tends to move at a large angle, which shows that the ZnSe shell is successfully coated. Figure 2 It can be seen that the new method of the present application can achieve the size of ZnSe / ZnS quantum dots and the sea urchin-like morphology displayed by regulation, and the particle size is uniform; Figure 3 It can be seen that the device has a lower turn-on voltage and better external quantum efficiency (EQE).
[0044] The present invention synthesizes a large-size ZnSe core by using DPP-Se (selenium dissolved in diphenylphosphine) precursor and ODE-Se (selenium dissolved in octadecene) precursor in sequence, and then coats the ZnS shell outside the crystal core with TOP-S (sulfur dissolved in trioctylphosphine) and OT (octanethiol) precursor in sequence, and finally obtains a large quantum dot size, thereby reducing the energy of the excitation photon, and finally making the quantum dot luminescence peak red-shift to the positive blue light range (450-470nm). In addition, the reaction temperature of this synthesis method is high, and the obtained quantum dots are a kind of sea urchin-like structure with multi-angle shape, and the quantum dots of this structure have a larger specific surface area, and its light absorption capacity is enhanced, which means that this quantum dot has higher efficiency in photoluminescence and electroluminescence applications. At the same time, the larger specific surface area also contributes to the rapid transmission and distribution of heat and charge. For displays working under high brightness and high power conditions, the improvement of this heat dissipation performance can extend the life of the quantum dots and maintain the long-term stability and performance of the display. The synthesis method adopted by the present invention is different from the synthesis method of ZnSe / ZnS quantum dots in the prior art. The principle of the preparation method proposed by the present invention is based on the formula of traditional nucleation theory: r*=2γVm / RTlnS, (where r* is the critical nucleation radius of the crystal, γ is the surface energy, and S is the supersaturation of the solution). According to the formula, the critical nucleation radius of the crystal is proportional to the surface energy γ. In order to obtain a larger crystal, a highly reactive ligand is required to increase its critical nucleation radius. The principle of the preparation method of sea urchin-shaped ZnSe / ZnS quantum dots proposed by the present invention is to use a highly reactive DPP-Se precursor to synthesize a large-sized ZnSe seed with a diameter of 3.5nm, and then use a relatively less reactive ODE-Se precursor to grow the seed into a ZnSe nucleus with a diameter of 8nm. After being coated with a ZnS shell, the crystal diameter grows to 13nm, and the emission peak position is red-shifted to 460nm. The application of the sea urchin-shaped ZnSe / ZnS quantum dots prepared by the preparation method of the present invention is: LED light-emitting devices are made based on the quantum dots as the light-emitting layer, and good blue light LED performance is obtained. The quantum dots prepared by the method have good application potential in the field of photoelectric luminescence.
[0045] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing sea urchin-shaped ZnSe / ZnS quantum dots, It is characterized in that The following steps are involved: Step 1: Prepare ZnSe seeds using Se-DPP precursor; Step 2: injecting Zn and Se precursors dissolved in ODE into the ZnSe seed solution prepared in step 1 to obtain ZnSe cores; Step 3: Inject TOP-S precursor and OT precursor into the ZnSe core solution prepared in step 2 respectively to obtain sea urchin-shaped ZnSe / ZnS quantum dots.
2. The method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to claim 1, It is characterized in that In step 1, the specific method for preparing ZnSe seed crystals is: injecting Se-DPP precursor into a mixed solution of zinc acetate, oleic acid, oleylamine and liquid paraffin.
3. The method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to claim 1, It is characterized in that When the Se-DPP precursor was injected, the temperature was stabilized at 280-320 °C.
4. The method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to claim 1, It is characterized in that In step 2, during the preparation of the ZnSe core, the temperature is maintained at 280-320° C., and the volume ratio of the injected Zn precursor mixture dissolved in ODE to the injected Se precursor mixture dissolved in ODE is (4-6):(2-3).
5. The method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to claim 1, It is characterized in that In step 3, the temperature when injecting the TOP-S precursor is maintained at 280-320°C; the temperature when injecting the OT precursor is maintained at 260-300°C.
6. The method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to claim 1, It is characterized in that In step 3, the volume ratio of the injected amounts of TOP-S precursor and OT precursor is (2-3):(4-6).
7. Application of sea urchin-shaped ZnSe / ZnS quantum dots, It is characterized in that The sea urchin-shaped ZnSe / ZnS quantum dots are prepared by the method for preparing sea urchin-shaped ZnSe / ZnS quantum dots according to any one of claims 1 to 6, and the sea urchin-shaped ZnSe / ZnS quantum dots are used in light-emitting devices.
8. The use of the sea urchin-shaped ZnSe / ZnS quantum dots according to claim 7, It is characterized in that The structures of the light-emitting device are ITO (indium tin oxide) / PEDOT:PSS [poly (3,4-ethylenedioxythiophene) / poly (styrene sulfonate)] / TFB {poly [(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)]} / quantum dots / PO-T2T {2,4,6-tris [3- (diphenylphosphino)phenyl] -1,3,5-triazine} / LiF / Al.
9. The use of the sea urchin-shaped ZnSe / ZnS quantum dots according to claim 8, It is characterized in that The preparation method of the light emitting device comprises the following steps: firstly, in a nitrogen atmosphere, a hole transport layer PEDOT:PSS and a TFB layer of the device are prepared by spin coating on an etched ITO conductive glass; then, a quantum dot layer is prepared by spin coating; and then, a 6.5×10 -7 Under the high vacuum of the tortoise, the device's electron transport layer PO-T2T and electrode LiF / Al layer are sequentially evaporated into films by a thermal evaporation system.
10. The use of the sea urchin-shaped ZnSe / ZnS quantum dots according to claim 9, It is characterized in that The speed of spin coating PEDOT:PSS, TFB and quantum dot layers was 1000-4000 r / min, and the spin coating time was 30-60 s; The thickness of the evaporated PO-T2T layer is 20-60 nm, the thickness of the evaporated LiF layer is 1-2 nm, and the thickness of the evaporated Al layer is 80-150 nm.
